Sports analytics analysis, visualisation and decision making in sports performance - Jayal, Ambikesh; McRobert, Allistair; O'Donoghue, Peter; Oatley, Giles (Routledge studies in sports performance analysis, 2018)
As the analysis of big datasets in sports performance becomes a more entrenched part of the sporting landscape, so the value of sport scientists and analysts with formal training in data analytics grows. Sports Analytics: Analysis, Visualisation and Decision making in Sports Performance provides the most authoritative and comprehensive guide to the use of analytics in sport and its application in sports performance, coaching, talent identification and sports medicine available. Employing an approach-based structure and integrating problem-based learning throughout the text, the book clearly defines the difference between analytics and analysis and goes on to explain and illustrate methods including: Interactive visualisation; Simulation and modeling; geospatial data analysis; Spatiotemporal analysis; Machine learning; Genomic data analysis; Social network analysis. Offering a mixed-methods case study chapter, no other book offers the same level of scientific grounding or practical application in sports data analytics. Sports Analytics is essential reading for all students of sports analytics, and useful supplementary reading for students and professionals in talent identification and development, sports performance analysis, sports medicine and applied computer science.